Control of sympathetic activity - new insights; new therapeutic targets? - Ritz, Eberhard; Rump, Lars Christian (Nephrology, dialysis, transplantation, 2010)
Recently, a large international group of 25 investigators identified a candidate gene for hypertension which codes for phosducin (Pdc) as a novel player in the sympathetic nervous system [1]. In their study, a wide spectrum of findings documented its so-far unrecognized and apparently important role in experimental and human stress-induced hypertension. This conclusion is based on data ranging from detailed analyses of the sympathetic system in genetically manipulated Pdc −/− (knock-out) mice to the demonstration of its relevance in humans: in two separate cohorts, French Canadian and Afro-American individuals, respectively, a correlation was documented between single-nucleotide polymorphisms (SNPs) in the Pdc gene and stress-dependent blood pressure reactions.